Bank incentives and the effect of the paycheck protection program - Gustavo Joaquim; Felipe Netto (Federal Reserve Bank of Boston, 2021)
We assess the role of banks in the Paycheck Protection Program (PPP), a large and unprecedented smallbusiness support program instituted as a response to the COVID-19 crisis in the United States. In 2020, the PPP administered more than 525 billion in loans and grants to small businesses through the banking system. First, we provide empirical evidence of heterogeneity in the allocation of PPP loans. Firms that were larger and less affected by the COVID-19 crisis received loans earlier, even in a within-bank analysis. Second, we develop a model of PPP allocation through banks that is consistent with the data. We show that research designs based on bank or regional shocks in PPP disbursement, common in the empirical literature, cannot directly identify the overall effect of the program. Bank targeting implies that these designs can, at best, recover the effect of the PPP on a set of firms that is endogenous, changes over time, and is systematically different from the overall set of firms that ultimately receive PPP loans. We propose and implement a model-based method to estimate the overall effect of the program and find that the PPP saved 7.5 million jobs.
Keywords: H81; G28; J21; E24; 330; Paycheck Protection Program; COVID-19; small business lending; financial frictions